Formalist Art Criticism and the Politics of Meaning - Tekiner, Deniz (Social justice, 2006)
Part of a special issue on art, power, and social change. Art criticism was dominated by formalism in the U.S. during the years following World War II. This was a time when the focus of the Western art world shifted from Paris, France, to New York, while the U.S. experienced an economic boom, political life was characterized by complacency, and dissent was barely tolerated. From the late 1940s to the late 1960s, formalism worked to appropriate modern art to the market interests and conventional sensibilities of the art world. Indeed, formalism helped to uphold conservative agendas through its support of the market apparatus and its invalidation of social concerns as expressed through art. By focusing on form alone, it obscured the relationship between art and social contexts and the socially critical implications of art.